Removal of Methylene Blue from an Aqueous Medium Using Atemoya Peel as a Low-cost Adsorbent - Venceslau, Adneia de Fátima Abreu; Mendonça, Andressa Campos; Carvalho, Lucas Bragança [UNESP]; Ferreira, Guilherme Max Dias; Thomasi, Sergio Scherrer; Pinto, Luciana Matos Alves (Springer Nature, 2021)
This study prepared a biosorbent from the agricultural waste of atemoya peels, which was then used to remove the methylene blue dye. The atemoya peels were used in natura, and some were subjected to an alkaline treatment. The pH values obtained for the points of zero charge were 6.0 and 8.0 for the untreated and alkaline-treated materials, respectively. For neutral and/or alkaline pH values, the untreated and treated materials achieved average removals of approximately 80% and 90%, respectively. A kinetic study of the model dye removal profile showed a higher removal ratio over a shorter period for the alkaline-treated material. This profile is described by the pseudo-second-order model, which was the best fit for the D-R isotherm in both biosorbents. The maximum biosorption capacities were 190.18 mg g−1 (untreated) and 264.50 mg g−1 (treated) at 45 °C, and the alkaline-treated materials were shown to be reusable for at least 5 cycles. The results show that these biosorbents are efficient and cost-effective to remove the studied model molecules.
Keywords: Adsorption; Annona; Biomass; Eco-friendly; Residue; Wastewater treatment